Presentations for From Farm to Table: Agrifood Systems and Trade Challenges in the Southern Cone - Piñeiro, Valeria; Elverdin, Pablo; Papendieck, Sabine; Pascuzzi, Nieves; Illescas, Nelson (2023)
Food systems around the world face serious social, nutritional, and environmental challenges, and must evolve to meet new, multiple, and interrelated objectives. As public policies are reshaped to support this transformation, two fundamental factors must be considered: